Using of concepts "conservatism & accrual" and their reflection in enhancing of quality of financial reporting - عبد الله, سلمان حسين; حسين, ميسون داود (Journal of Economics and Administrative Sciences, 2016)
The use of Conservatism  significant impacts on the financial statements and thus on financial reporting which is produced by these lists so Rate Some of the professionals that the principle of accounting while Rate of others as a constraint, and brought this category based on the uses of this restriction sometimes used the accountant this restriction and especially with the uncertainties in the Sometimes it may collide with some of the cases in which the accountant may be forced to leave in custody as a result of emergence of economic events that gave rise to rights or future commitments should be disclosed.The emergence in custody mainly was due to the uncertainty and its essence is to report on at least the values ​​of the assets, revenues and higher values ​​of the obligations and expenses, thereby imposing behavior pessimistic on the accountant at his choice between accounting measurement alternatives for the purposes of financial reporting and thus it will show users the product is real with the increase in demand for display objective and fair focuses attention on the priorities for the investor as a user of the information came to be seen as a constraint in custody stating its use in certain cases, such as those that require a personal rule by the accountant.